UPAYA PEMERINTAH TURKI DALAM MENGATASI GERAKAN SEPARATISME SUKU KURDI TAHUN 1984-2007 (THE EFFORTS BY TURKISH GOVERNMENT TO FIGHT FOR KURDS SEPARATISM IN 1984-2007) - handayani, andina sari (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret)
ABSTRACK This study aimed to describe: (1) Background ethnic Kurdish separatist movement in the country of Turkey; (2) Ethnic Kurdish separatist movements in the country of Turkey; and (3) The Impact and the Turkish government's efforts in addressing the tribal Kurdish separatist movement. This study uses historical method with heuristic measures, criticism, interpretation, and historiography. The data collection technique is the technique of literature by using the system catalogs or computers and resume use of the Internet. The data analysis technique used is the historical analysis technique with external and internal criticism. The conclusions of this study are as follows. First, the Kurdish separatist movement in Turkey for autonomy began March 21, 1984, when the ban celebrations Nevros (Kurdish new year celebration). Second, the Kurdish separatist movement in Turkey gathered in the PKK. Third, the Turkish government policy on reducing negative sanctions against the PKK in the field of socio-cultural, economic, and law can not resolve the conflict between the government and ethnic Kurds. Key words: otonomy, Kurdi, separatist, ethnic, policy, Nevros